DESIGN AND IMPLEMENTING AN INSTRUMENT FOR PSYCHOPHYSIOLOGYCAL DIAGNOSIS (CASE OF ELECTRODERMAL ACTIVITY) - MEDENOU, DATON; Vodounou, Marnie (My University, 2011)
Advances in electronics, and particularly in instrumentation have made possible the modernization of medical equipment and the emergence of neuroimaging. However despite the groundwork laid by Fere and Tarchanoff since 1888, a delay occurs in the field of psychophysiology. In this paper we describe a new instrument based on FERE’s method, designed and implemented for EDA’s record and analysis. The hard and soft parts of the instrument are based on the skills of microcontroller ATmega168. An amplitude analysis achieves the diagnosis skills of the instrument.
Keywords: EDA; endosomatic method; FERE method; ATmega 168; psychophysiology